Event-Triggered Controller Design for Autopilot with Input Saturation. (16th June 2020) - Xia, Guoqing; Xia, Xiaoming; Bo, Zhao; Sun, Xianxin; Sun, Chuang
Abstract : This paper considers the problem of autopilot design for surface ship with environmental disturbances and input saturation. Extended state observer (ESO) is used to reconstruct yaw rate and estimate unknown environmental disturbances. An auxiliary dynamic system is employed to handle the input saturation. By combining with the auxiliary dynamic system and ESO, an event-triggered controller (ETC) is designed, and energy is saved by reduction in the rudder rate. Simulation results illustrate the effectiveness and feasibility of the event-triggered proposed controller.